Self-interacting dark matter - Mavromatos, Nick E. (2017)
Self-interacting dark matter (SIDM) is a hypothetical form of dark matter (DM), characterized by relatively strong (compared to the weak interaction strength) self-interactions (SIs), which has been proposed to resolve a number of issues concerning tensions between simulations and observations at the galactic or smaller scales. We review here some recent developments discussed at the 14th Marcel Grossmann Meeting (MG14), paying particular attention to restrictions on the SIDM (total) cross-section from using novel observables in merging galactic structures, as well as the rôle of SIDM on the Milky Way halo and its central region. We report on some interesting particle-physics inspired SIDM models that were discussed at MG14, namely the glueball DM, and a right-handed neutrino DM (with mass of a few tens of keV, that may exist in minimal extensions of the standard model (SM)), interacting among themselves via vector bosons mediators in the dark sector. A detailed phenomenology of the latter model on galactic scales, as well as the potential role of the right handed neutrinos in alleviating some of the small-scale cosmology problems, namely the discrepancies between observations and numerical simulations within standard ΛCDM and ΛWDM cosmologies are reported.